Environmental Health Risks and Public Policy: Decision Making in a Free SocietyEnvironmental Health Risks and Public Policy: Decision Making in a Free Society, by BatesDavid V. Seattle: University of Washinaton Press, 1994. - Wokutch, Richard E. (Academy of Management Review, 1995)
The article reviews the book ?Environmental Health Risks and Public Policy: Decision Making in a Free Society,? by David V. Bates.